THE VALIDITY OF THE ESTABLISHMENT OF THE LEGAL ENTITY STATUS OF THE VILLAGE-OWNED ENTERPRISE “SUMBER REJEKI” LATUKAN VILLAGE : JURIDICAL REVIEW - Erda Zenta Priscilasari; Adang Moelyono; Abid Muhtarom (EQUALEGUM International Law Journal, 2023)
Background. The establishment of village-owned enterprises (hereinafter abbreviated as Bumdes) is based on the needs and potential of the village as an effort to improve community welfare. This business entity is intended to encourage or accommodate all activities related to increasing the income of the village community. This study aimed to determine the procedures in the formation of Bumdes that are legal entities and to determine and analyze the legal consequences of Bumdes that obtain ratification from the Ministry of Law and Human Rights (hereinafter abbreviated as Kemenkumham), the validity of  business entities to become legal entities, the authority of ratification and the legal consequences of Bumdes that do not meet the requirements of ratification in Kemenkumham. Research Method. This research was a normative research that uses a normative juridical approach, this approach is carried out by examining all laws and regulation number 11 of 2021 concerning Bumdes that are related to the problem (legal issue) being studied. Findings. The consistency and suitability of one law with another in Bumdes that are not registered with the PDTT Ministry of Villages and are not also authorized by Kemenkumham are in fact still running as ordinary business entities but are not free to develop business. Conclusion. The establishment and registration of Bumdes as legal entities is to facilitate village partnerships, facilitate the promotion of regional potential, accelerate regional economic improvement.